Increases in Human Papillomavirus Vaccination Among Adolescent and Young Adult Males in the United States, 2011–2016. (23rd March 2018) - Patel, Eshan U; Grabowski, M Kate; Eisenberg, Anna L; Packman, Zoe R; Gravitt, Patti E; Tobian, Aaron A R
Abstract : Temporal trends in human papillomavirus vaccine coverage were assessed among 2011–2016 National Health and Nutrition Examination Surveys participants aged 9–26 years. Coverage substantially increased among males, but minimal gains were observed among females. Coverage remains below national targets. Abstract: In the United States, human papillomavirus (HPV) vaccination has been recommended for females since 2006 and males since 2011. We assessed temporal trends in HPV vaccine coverage (defined as receipt of ≥1 dose) among 9–26-year-old participants in the 2011–2016 National Health and Nutrition Examination Surveys. While coverage increased overall, from 37.7% to 45.7%, among females (adjusted prevalence difference [aPD], 7.1%; 95% confidence interval [CI], .1%–13.7%), there was no change among female adolescents aged 9–17 years. For males, coverage increased overall, from 7.8% to 27.4% (aPD, 18.8%; 95% CI, 14.1%–23.5%), and among every stratum of age, race/ethnicity, health insurance status, poverty level, and immigration status ( P ≤ .05). The increase in HPV vaccine coverage observed among males is encouraging, but coverage remains below national targets for both males and females.